Evaluation of the temperature effect on vegetable oils by chemical analysis and ultraviolet-visible spectroscopy (Bioscience Journal, 2018)
Several methodologies could be used to characterize vegetable oil besides estimating thermal modification provided by high temperatures. These techniques are used as a proper tool to determine compositional and functional analysis of food ingredients and finished products. In general, vegetable oils are extracted from seeds like the rapeseed (canola oil) soybean (soybean oil), among others. In the current work vegetable oils such as canola and soybean were heated at a temperature of 100°C from 1h up to 28 h and the degraded products were measured to assess the oil stability at temperature. The determination of acid number, peroxide value and iodine number by chemical analysis was carried out for the estimation of the oxidative heat stability of these oils. Ultraviolet-visible spectroscopy strategy was also used to better comprehend this phenomenon, since it greatly improve the performance of measurements, in order to step up sensitivity. The findings demonstrated that vegetable oils thermal deteriorated as seen in the batocromic displacement of the samples heated and increasing the specific absorption in 350 nm. These data were capable to highlight the differences observed in the degree of unsaturation of oils.